Defibrotide for the Treatment of Veno‐Occlusive Disease/Sinusoidal Obstruction Syndrome in Paediatric Patients Who Did Not Receive Haematopoietic Stem Cell Transplantation: Case Reports of Patients From a German Academic Hospital - Katharina Kleinschmidt; Anja Troeger; Jürgen Föll; Tarek Hanafee‐Alali; Marcus Jakob; Sonja Kramer; Silke Kietz; Selim Corbacioglu (eJHaem)
ABSTRACT Introduction Veno‐occlusive disease/sinusoidal obstruction syndrome (VOD/SOS) is a potentially life‐threatening condition characterised by obstruction of the small veins of the liver. Although typically associated with haematopoietic stem cell transplantation, VOD/SOS may also occur following intensive multimodal chemotherapy regimens. In children, symptoms of VOD/SOS are refractory thrombocytopaenia, weight gain, hepatomegaly, ascites and fluid retention, hyperbilirubinaemia and sometimes right upper quadrant pain. Methods Here, we present a case series of six paediatric patients with acute lymphoblastic leukaemia who developed severe VOD/SOS while receiving standard AIEOP‐BFM ALL protocol treatment. Results/Conclusions All patients responded promptly to defibrotide treatment and exhibited favourable clinical outcomes. Trial Registration The authors have confirmed clinical trial registration is not needed for this submission